Brucella abortus triggers the differential expression of immunomodulatory lncRNAs in infected murine macrophages - Flores-Concha, Manuel; Gómez, Leonardo A.; Soto-Shara, Rodrigo; Molina, Raúl E.; Coloma-Rivero, Roberto F.; Montero, David A.; Ferrari, Ítalo; Oñate, Ángel (Frontiers in Immunology, 2024)
The lncRNAs (long non-coding RNAs) are the most diverse group of non-coding RNAs and are involved in most biological processes including the immune response. While some of them have been recognized for their influence on the regulation of inflammatory activity, little is known in the context of infection by Brucella abortus, a pathogen that presents significant challenges due to its ability to manipulate and evade the host immune system. This study focuses on characterize the expression profile of LincRNA-cox2, Lethe, lincRNA-EPS, Malat1 and Gas5 during infection of macrophages by B. abortus. Using public raw RNA-seq datasets (sequence reads) from BMM cells infected with B. abortus we constructed for the first time a novel and complete lncRNA expression profile in a primary macrophage Brucella-infected. In addition, from public RNA-seq raw datasets of RAW264.7 cells infected with B. abortus we constructed a transcriptomic profile of lncRNAs in order to know the expression of the five immunomodulating lncRNAs studied here at 8 and 24 h postinfection. Finally, we performed in vitro infection assays in RAW264.7 cells and peritoneal macrophages to detect by qPCR significant changes in the expression of these lncRNAs at first 12 hours post infection, a key stage in the infection cycle where Brucella modulates the immune response to survive. Our results demonstrate that B. abortus induces significant changes in the expression of these immunomodulatory lncRNAs and suggest a potential involvement of these lncRNAs in the immune evasion strategy employed by Brucella to facilitate its intracellular survival.